Iron-induced derangement in hepatic Δ-5 and Δ-6 desaturation capacity and fatty acid profile leading to steatosis: Impact on extrahepatic tissues and prevention by antioxidant-rich extra virgin olive oil. (February 2020) - Barrera, Cynthia; Valenzuela, Rodrigo; Rincón, Miguel A.; Espinosa, Alejandra; López-Arana, Sandra; González-Mañan, Daniel; Romero, Nalda; Vargas, Romina; Videla, Luis A.
Highlights: Iron-rich diet (IRD) induces oxidative stress, hepatic steatosis, and n-3 and n-6 long-chain polyunsaturated fatty acids (LCPUFAs) depletion in the liver and extrahepatic tissues. Depletion of liver LCPUFAs (especially n-3) determines a low fatty acid oxidation over a high de novo lipogenesis. Antioxidant-rich extra virgin olive oil (AR-EVOO) in diet abolishes all the changes induced by IRD. Beneficial effects of AR-EVOO are important to avoid steatosis progression into the more severe steatohepatitis, cirrhosis and hepatocellular cancer. Abstract: The administration of iron induces liver oxidative stress and depletion of long-chain polyunsaturated fatty acids (LCPUFAs), n-6/n-3 LCPUFA ratio enhancement and fat accumulation, which may be prevented by antioxidant-rich extra virgin olive oil (AR-EVOO) supplementation. Male Wistar rats were subjected to a control diet (50 mg iron/kg diet) or iron-rich diet (IRD; 200 mg/kg diet) with alternate AR-EVOO for 21 days. Liver fatty acid (FA) analysis was performed by gas-liquid chromatography (GLC) after lipid extraction and fractionation, besides Δ-5 desaturase (Δ-5 D) and Δ6-D mRNA expression (qPCR) and activity (GLC) measurements. The IRD significantly ( p  < 0.05) increased hepatic total fat, triacylglycerols, free FA contents and serum transaminases levels, with diminution in those of n-6 and n-3 LCPUFAs, higher n-6/n-3 ratios, lower unsaturation index and Δ5-D and Δ6-D activities, whereas the mRNA expression of both desaturases was enhanced over control values, changes that were prevented by concomitant AR-EVOO supplementation. N-6 and n-3 LCPUFAs were also decreased by IRD in extrahepatic tissues and normalized by AR-EVOO. In conclusion, AR-EVOO supplementation prevents IRD-induced changes in parameters related to liver FA metabolism and steatosis, an effect that may have a significant impact in the treatment of iron-related pathologies or metabolic disorders such as non-alcoholic fatty liver disease. Graphical abstract: Image, graphical abstract